Polityka kadrowa wobec osób niepełnosprawnych na podstawie badań wybranych pracodawców i pracowników - Jakobsze, Adam; Ober, Józef (Polityka i Społeczeństwo, 2020)
The aim of the article is to identify the reasons for low employment rates of people with disabilities in Poland, and to examine whether employers, disabled employees and other staff want to talk about the rational use of the rights of a disabled employee and what views, opinions or other circumstances can make it difficult. Four hypotheses were formulated in the work, which were verified on the basis of surveys and interviews conducted in the period from March to September 2017 in the Voivodship of Silesia. The considerations were rounded off with conclusions and comments.